Process development for grid generations to simulate hypersonic flow around a generic re-entry capsule - Krishna Contractor (2016)
After the retirement of the Space shuttle, space agencies around the world have turned to space return capsules for re-entry missions. During re-entry into the atmosphere, the capsule undergoes manoeuvres at extremely high speeds reaching 20 Mach and beyond. At such hypersonic conditions, several flow features occur around the capsule such as, bow shocks resulting in high heat loads and pressure gradients which in tum results in dissociation and ionization of chemical molecules in air, boundary layer transition from laminar to turbulent, expansion fans and shear layers. During the design phase, the accurate prediction of these flow features is extremely crucial. Experimental verification of these cumulative effects becomes extremely difficult and with increasing budget cuts in space research, it is not the most viable option for the prediction of the effects. As an efficient alternative, several computational methods have been developed over the past 40 years to predict flow features at hypersonic conditions. The purpose of this study is to develop an optimal blocking strategy to predict the flow around a generic Apollo space-return capsule. The study uses an iterative procedure of domain size and mesh adaptions followed by steady state simulations to optimize the number of grid points as well as the number of blocks in which the domain has been split. The meshing software being used is ICEM CFD and the simulations are done with the commercially available implicit flow solvers Fluent and CFX.